(untitled) (The Agriculturists, 2019)
An experiment was conducted at the growth chamber of Department of Crop Botany in the Bangladesh Agricultural University, Mymensingh, Bangladesh during March 2018 to observe morpho-physiology and anatomical response of sorghum. Six genotypes were grown in hydroponics with a full nutrient solution (NH4NO3-500 μM; Ca(NO3)2-500 μM; MgSO4-200 μM; KH2P04 -100 μM; FeC13-2μM; H2B03-11 μM; MnC12-2μM; ZnC12-0.35μM; CuCl2-0.2μM; (NH4)6Mo704-0.1 μM) and 100 mM salinity was imposed on 14 days seedlings. Data on morpho-physiological and anatomical parameters from seedlings were collected after 21 days and stress tolerant indexes of shoot and root were analyzed. Anatomical parameters like metaxylem and protoxylem thickness were also investigated. The results indicated that all the parameters viz. root length, shoot length, fresh and dry weight of shoot and root, stress tolerance index of root, and shoot, dry weight of shoot and root, relative chlorophyll content, photochemical efficiency (Fv/Fm), proline concentration, total root area, vascular cylinder area and root diameter were decreased with increasing salinity levels except leaf proline content. Genotypes BD 750 and BD 686 showed better performance considering tolerant indicators while the poor performance was exhibited by BD 747 and BD 753. Thus, based on overall observation BD 750 and BD 686 might be salt tolerant. The Agriculturists 2019; 17(1-2) 52-65